A retrospective analysis of the clinical characteristics of 207 hospitalized children with adrenal masses - Zhang, Kaiping; Zhang, Ye; Zhang, Yin; Chao, Min (Frontiers in Pediatrics, 2023)
Objective The detection rates of adrenal masses (AMs) have recently increased. The present study aimed to examine the clinical characteristics of these adrenal masses for guiding the clinical diagnosis and treatment among hospitalized children. Methods The clinical data of AM cases admitted to our hospital from January 2014 to March 2023 were collected and analyzed retrospectively. The data included composition, sex, age, initial presentation, size and site of mass, functional tumor, intervention or surgery, pathological or clinical diagnosis, and imaging data. Results A total of 207 hospitalized children were included. Among them, adrenal hematoma was the most common finding (53.6%), followed by adrenal neuroblastoma (36.2%). Most masses were larger-sized (51.2%) and non-functional (94.7%). We found that adrenal hematoma commonly occurred in a neonate or child with abdominal trauma. Most adrenal hematoma cases were found in male patients (63.1%), on the right side (71.2%), and with sizes <4 cm (73.9%). Adrenal neuroblastoma was commonly detected in male patients (56.0%), on the right side (66.7%), and with sizes ≥4 cm (85.3%). Moreover, the metastases were frequently explored at the time of diagnosis. In addition, there was no significant difference between ultrasound and computed tomography (CT) scans under suspicion of hematoma (P > 0.05). However, CT showed a priority over ultrasound in the diagnosis of neuroblastoma (P < 0.05). Conclusion Most masses were non-functional and benign. Of these, adrenal hematoma was the most common type of pediatric AM, followed by adrenal neuroblastoma. They were both commonly found in male patients and on the right side. Neuroblastoma revealed a larger tumor size. Compared to cases of adrenal hematoma, cases of adrenal neuroblastoma required CT scans for further assessment.